Conjunction Analysis of Gramatical Cohesion on Christine Lindop’s Bridge and Other Love Stories - Siti Marfu'ah; Khristianto Khristianto (JSSH (Jurnal Sains Sosial dan Humaniora), 2023)
This study aims to describe the forms of grammatical cohesion conjunctions  in a short story book entitled The Bridge and Other Love Stories by Christine Lindop. This study focused on the forms of conjunctions, meanings, and grammatical cohesion functions by using Halliday's theory to analyze the data. The approach used in this study was descriptive qualitative to analyze every word contained in the short story entitled The Bridge and other love stories by Christine Lindop. The results of this study indicate that the forms of grammatical cohesion conjunctions contained in the short story book with that title are Additive, Adversative, Causal, and Temporal conjunctions. The meaning and function of each cohesion are 1) meaningful as a sequential connecting time, 2) shows the cause of something, 3) shows the event that contrasts with the situation, 4) shows a choice. This research can be a reference for academics for further research in the same field with different objects in the future.